STUDY OF SOFT CLAY SOIL TREATMENT USING COMBINATION OF PVD AND GEOTEXTILE WOVEN CASE STUDY: BOGOR - SERPONG JORR-3 TOLL ROAD PROJECT PLANNING - Aditya Wuladarman, Resnu
The planned of Jakarta Outer Ring Road (JORR)-3 Toll Road with a total length of 31 km, which connects Bogor City and Serpong City, through a subgrade consisting of 17 km of soft clay and 14 km of medium clay. Soil investigations that have been carried out are 30 points of sondir test, 13 points of geotechnical drilling, and laboratory tests. The main road from STA 1+000 to STA 16+700 is dominated by soft clay arround 8 meters thickness and it is found arround 2 meters depth from the surface. Common borrow materials with a thickness up to 15 meters is needed to achieve the design elevation requirement. The combination method of PVD and geotextile was chosen to accelerate the subgrade consolidation settlement and maintain the stability of the embankment. Analysis using two-dimensional finite element method was carried out to determine the stages of work that resulted in a subsidence profile of the embankment surface and stability by toll road acceptance standards. This study also evaluates the reduction of soil permeability due to the smear effect around PVD and its effect to the duration and the amount of settlement.